Strategi Permintaan Maaf dalam Interaksi Jual Beli Etnis Madura: Kajian Etnocyberpragmatik - Putikadyanto, Agus Purnomo Ahmad; Djodjok Soepardjo; Mulyono; Savitri, Agusniar Dian (IAIN Madura, 2025)
This study examines the apology speech strategies in online buying and selling interactions within the Madurese ethnic community using an ethnocyberpragmatic approach. Apologies are a crucial aspect of interpersonal communication, reflecting politeness, ethics, and efforts to maintain social harmony. In the context of cattle trading conducted via social media platforms such as YouTube, the Madurese people display distinct linguistic practices. The data were collected through non-participant observation of 200 YouTube Shorts videos depicting cattle trading interactions uploaded on the “Dunia Sapi” social media account. The findings reveal that the apology strategies employed include expressions of regret, direct apologies, reasoning, acknowledgment of fault, as well as newly identified strategies such as warnings and reproaches—elements not found in the CCSARP (Cross-Cultural Speech Act Realization Project) model. These results indicate that digital media does not erase local cultural traces but instead serves as a new space for expressing cultural values in online communication. This study underscores the importance of understanding linguistic dynamics in digitally mediated social interactions and expands cross-cultural pragmatic studies through an approach that integrates ethnographic and pragmatic analysis in the context of ethnic online communication.